Impact of support from social network on entrepreneurial intention of fresh business graduates : A structural equation modelling approach - Muhammad Shoaib, Farooq; Maimoona, Salam; Saif ur, Rehman; Fayolle, Alain; Norizan, Jaafar; Kartinah, Ayupp (Emerald Publishing Limited, 2018)
Purpose – Developing on the base of theory of planned behaviour (TPB), the purpose of this paper is to investigate the relationship between perceived social support (SS) from one’s social network and entrepreneurial